Genomic variation responding to artificial selection on different lines of Pekin duck - Xinye Zhang; Fangxi Yang; Jinxin Zhang; Tao Zhu; Xiurong Zhao; Yuchen Liu; Junhui Wen; Hongchang Gu; Gang Wang; Xufang Ren; Anqi Chen; Lujiang Qu (Poultry Science)
Understanding the genomic variation in Pekin duck under artificial selection is important for improving the utilization of duck genetic resources. Here, the genomic changes in Pekin duck were analyzed by using the genome resequencing data from 96 individual samples, including 2 conservation populations and 4 breeding populations with different breeding backgrounds. The population structure, runs of homozygosity (ROH), effective population number (Ne), and other genetic parameters were analyzed. The breeding populations showed lower genetic diversity compared to the conservation populations. Maple Leaf duck and Cherry Valley duck retained low genetic diversity compared to other breeding populations, with Cherry Valley duck showing the lowest diversity and the highest inbreeding coefficient. This suggested that Cherry Valley and Maple Leaf ducks have undergone intensive selection compared to other breeding populations. By the analysis of runs of homozygosity (ROHs), some genes (e.g., IGF1R) associated with growth traits were identified. By the analysis of the selection signal, strong selection characteristics in certain genomic regions during the breeding of Peking duck across different selected lines were observed. In addition, copy number variations (CNVs) in Pekin duck populations were analyzed. Six regions of interest were identified, containing RPA1, DOT1L, SLC25A42, RALYL, TRPA1, and IGFBP2. Furthermore, the allele frequency distribution of these genes showed significant differences between breeding populations and conservation populations, indicating that these candidate genes could have undergone strong selection pressure during long-term selection for improved production. These findings contribute to a deeper understanding of the distinct evolutionary processes in Pekin ducks under artificial selection and provide valuable insights for future breeding strategies.